BAYAT CERAMIC (AESTHETIC, FORM, AND FUNCTION) - Yustana, Prima (Acintya, 2014)
This study aims to examine the characteristics of ceramic products produced by the craftsmen in thecity of Klaten, especially in Bayat and the surrounding districts. Background of this research is theimportance of the existence of Bayat districts that are located between the city of Solo and Yogyakarta.They are supposed to be a major tourist destination but until now they are still not as crowded asKasongan in the city of Jogjakarta. In addition, another consideration in producing ceramic Bayat isfamous for using a tilted position round or often called perbot skewed.There are some intriguing questions founded in this research including: whether the ceramic productsproduced in Bayat under the influence of ceramic crafts center from the nearby towns; what are thevarious products produced by using oblique rotation tools; what kind of finishing techniques areused by the craftsmen in executing the final results of ceramic products; is there any natural finishingdevelopment in the area of ceramic craft center in Bayat and its surroundings and also other issuesconcerning the marketing of products. This study uses a qualitative research method that is supportedby data from several sampling craftsmen selected from representatives of the southern region of themain road and the north Pagerjurang main road. Interviews are also used in the data searching andsupported by the image data using a digital camera.The research is targeted to publish original ceramic products of Bayat and variations so that the datawill be useful for a promotional tour of the area in order to make it more widely known in thecommunity. Identification of ceramic products in Bayat and the surrounding districts in the study ofaesthetics, form and function are expected to provide a clear explanation whether the ceramic productsof Bayat is compiled in a book as a learning tool. Detailed product identification can be usedalso as a good reference for the craftsmen, community, artists and students to be able to developceramic products in particular way in order to become more attractive and innovative.Keywords: Bayat, Ceramic, Aesthetic form and function